2013
DOI: 10.1111/clr.12172
|View full text |Cite
|
Sign up to set email alerts
|

Effects of directly autotransplanted tibial bone marrow aspirates on bone regeneration and osseointegration of dental implants

Abstract: Directly autotransplanted tibial BM aspirates did not show beneficial regenerative effects in the small study population (N = 6) of the present pilot trial. However, the proximal tibia proved to be a potential donor site for small quantities of BM. Future trials should clarify whether concentration of tibial BM aspirates could effect higher regenerative potency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(82 citation statements)
references
References 43 publications
3
72
0
7
Order By: Relevance
“…of patients (age range)No. of maxillary sinuses evaluatedDonor site for BMACClinical findings/implant survivalTiming of biopsyHistologic outcomesde Oliveira et al [12]SCG (BMAC obtained by single centrifugation and bone graft)DCG (BMAC obtained by double centrifugation and bone graft)Control (xenogenous bone graft alone)15 (mean age 55.4 years)21Posterior iliac crest- 68 implants were placed in the previously grafted sites, and 100% osseointegrated- Loading was applied after 6 months6 monthsVital mineralized tissue:- SCG 38.44%- DCG 34.63%- Control 27.30%- Not statistically differentNon-vital mineralized tissue:- SCG 13.70%- DCG 19.63%- Control 22.79%- Not statistically differentNon-mineralized tissue:- SCG 47.87%- DCG 45.73%- Control 49.90%- Not statistically differentPasquali et al [7]Test (BMAC and xenogenous bone graft)Control (xenogenous bone graft alone)8 (mean age 55.4 years)16Superior posterior iliac crest- At least two implants were placed in each previously grafted sites, and all implants osseointegrated- Loading was applied after a 6-month healing period6 monthsVital mineralized tissue:- Test 55.15%- Control 27.30%- Statistically significantNon-vital mineralized tissue:- Test 6.32%- Control 22.79%- Statistically significantNon-mineralized tissue:- Test 38.53%- Control 49.90%- Not statistically significantPayer et al [2]Test (porous bovine bone mineral together with tibial bone marrow aspirate)Control (bovine bone graft without any additive)6 (mean age 58.2 years)12Tibia- 44 implants were stable and osseointegrated at radiographic and Periotest evaluation3 months6 monthsNewly formed bone:3 months-Test 10.36%- Control 9.45%- Not statistically significant6 months- Test 14.12%- Control 10.41%- Not statistically significant3 and 6 months:- Not statistically significantBone-to-bone substitute contact:3 months-Test 16.40%- Control 15.06%- Not statistically significant6 months- Test 20.26%- Control 17.89%- Not statistically significant3 and 6 months:- Not statistically significantSauerbier et al [11]Open bone marrow-derived mononuclear cell isolation by synthetic poylsaccharide (FICOLL) method with bovine bone mineral (BBM)Closed bone marrow aspirate concentrate (BMAC) system with BBMFICOLL group 4 (mean age 59.5 years)BMAC group 7(mean age 55 years)FICOLL group 6BMAC group 12Superior posterior iliac spine- 50 implants were placed (17 FICOLL group and 33 BMAC group)- Implant survival was evaluated after 1 year- No implant out of 17 was lost in the FICOLL group, before prosthetic loading- 1 implant out of 33 failed in the BMAC group, before prosthetic loading- No implant was lost after loading- All 49 osseointegrated implants were loaded and in function…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…of patients (age range)No. of maxillary sinuses evaluatedDonor site for BMACClinical findings/implant survivalTiming of biopsyHistologic outcomesde Oliveira et al [12]SCG (BMAC obtained by single centrifugation and bone graft)DCG (BMAC obtained by double centrifugation and bone graft)Control (xenogenous bone graft alone)15 (mean age 55.4 years)21Posterior iliac crest- 68 implants were placed in the previously grafted sites, and 100% osseointegrated- Loading was applied after 6 months6 monthsVital mineralized tissue:- SCG 38.44%- DCG 34.63%- Control 27.30%- Not statistically differentNon-vital mineralized tissue:- SCG 13.70%- DCG 19.63%- Control 22.79%- Not statistically differentNon-mineralized tissue:- SCG 47.87%- DCG 45.73%- Control 49.90%- Not statistically differentPasquali et al [7]Test (BMAC and xenogenous bone graft)Control (xenogenous bone graft alone)8 (mean age 55.4 years)16Superior posterior iliac crest- At least two implants were placed in each previously grafted sites, and all implants osseointegrated- Loading was applied after a 6-month healing period6 monthsVital mineralized tissue:- Test 55.15%- Control 27.30%- Statistically significantNon-vital mineralized tissue:- Test 6.32%- Control 22.79%- Statistically significantNon-mineralized tissue:- Test 38.53%- Control 49.90%- Not statistically significantPayer et al [2]Test (porous bovine bone mineral together with tibial bone marrow aspirate)Control (bovine bone graft without any additive)6 (mean age 58.2 years)12Tibia- 44 implants were stable and osseointegrated at radiographic and Periotest evaluation3 months6 monthsNewly formed bone:3 months-Test 10.36%- Control 9.45%- Not statistically significant6 months- Test 14.12%- Control 10.41%- Not statistically significant3 and 6 months:- Not statistically significantBone-to-bone substitute contact:3 months-Test 16.40%- Control 15.06%- Not statistically significant6 months- Test 20.26%- Control 17.89%- Not statistically significant3 and 6 months:- Not statistically significantSauerbier et al [11]Open bone marrow-derived mononuclear cell isolation by synthetic poylsaccharide (FICOLL) method with bovine bone mineral (BBM)Closed bone marrow aspirate concentrate (BMAC) system with BBMFICOLL group 4 (mean age 59.5 years)BMAC group 7(mean age 55 years)FICOLL group 6BMAC group 12Superior posterior iliac spine- 50 implants were placed (17 FICOLL group and 33 BMAC group)- Implant survival was evaluated after 1 year- No implant out of 17 was lost in the FICOLL group, before prosthetic loading- 1 implant out of 33 failed in the BMAC group, before prosthetic loading- No implant was lost after loading- All 49 osseointegrated implants were loaded and in function…”
Section: Resultsmentioning
confidence: 99%
“…For vital mineralized bone, these studies reported variable statistical significance. At 3–4 months, new bone formation for BMAC groups with controls [2, 14, 15] using no BMAC was 7.4–12.6% and for the control groups was 9.45–14.3%. At 6 months, new bone formation for BMAC groups [2, 15] was 13.5–14.12% and for control groups was 10.41–13.9%.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations